Komponen Penunjang Kurikulum Pendidikan Agama Islam - Nuruzzahri, Nuruzzahri (Multiverse: Open Multidisciplinary Journal, 2024)
This study investigates the supporting components of the Islamic Education curriculum, focusing on the elements that enhance its effectiveness and relevance in contemporary educational contexts. The research problem centers on identifying and evaluating the critical supporting components that contribute to a robust and comprehensive Islamic Education curriculum. Employing a qualitative research method, the study collects data through in-depth interviews with educators, curriculum experts, and policymakers, as well as analyzing relevant curriculum documents and classroom observations. The findings indicate that key supporting components include teacher competency, instructional materials, learning environment, assessment methods, and community involvement. These components significantly impact the quality and implementation of the Islamic Education curriculum, ensuring that it meets educational goals and student needs. The study concludes that a well-rounded Islamic Education curriculum requires not only a strong foundational structure but also the integration of these supporting components to foster holistic student development and effective learning outcomes. The research highlights the need for continuous improvement and adaptation of the curriculum to address evolving educational challenges and opportunities.